Tonsilitis Akut pada Anak : Laporan Kasus - Aisyah Lubis; Mukhlis Imanto (Medula, 2026)
Acute tonsillitis is a common ENT disease in children, characterized by sudden inflammation of the tonsils due to viral or bacterial infections. This condition can cause impaired swallowing, breathing, sleep, and reduce children's quality of life if not properly treated. We report a case of a 9-year-old boy with painful swallowing for 5 days, accompanied by fever, cough, runny nose, and snoring. Physical examination revealed T3-T3 tonsillar enlargement, bilateral hyperemia (+/+), no detritus, and no lymphadenopathy. The patient's Centor score was 1, leading to a diagnosis of acute tonsillitis of viral etiology. The patient received symptomatic therapy (paracetamol, rest, hydration, warm salt water gargling, and education) without antibiotics.